1983
DOI: 10.1152/jn.1983.50.4.798
|View full text |Cite
|
Sign up to set email alerts
|

Lateral geniculate nucleus unitary discharge in sleep and waking: state- and rate-specific aspects

Abstract: The relationship between behavioral state, discharge pattern, and discharge rate was investigated in 26 lateral geniculate nucleus (LGN) units recorded in cats in the dark during waking (W), synchronized sleep (S), and desynchronized sleep (D). A distinctive state-dependent discharge pattern was the presence of stereotyped bursts of 2-7 spikes that occurred in 63% of the units. These bursts were most frequent in S, much less frequent in D, and rarely occurred in W. Lack of association with discharge rate chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
106
0
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(120 citation statements)
references
References 0 publications
13
106
0
1
Order By: Relevance
“…These criteria picked out stereotypical patterns of spike firing and identified burst firing with the same properties as those previously recorded in vitro in other mammals. In particular, burst length depended on the duration of the initial within-burst ISI (McCarley et al, 1983;Radhakrishnan et al, 1999), and intraburst ISIs gradually increased in duration (McCarley et al, 1983;Radhakrishnan et al, 1999;Reinagel et al, 1999) (data not shown).…”
Section: Methodsmentioning
confidence: 92%
“…These criteria picked out stereotypical patterns of spike firing and identified burst firing with the same properties as those previously recorded in vitro in other mammals. In particular, burst length depended on the duration of the initial within-burst ISI (McCarley et al, 1983;Radhakrishnan et al, 1999), and intraburst ISIs gradually increased in duration (McCarley et al, 1983;Radhakrishnan et al, 1999;Reinagel et al, 1999) (data not shown).…”
Section: Methodsmentioning
confidence: 92%
“…These changes alter transmission of signals conveying information from external environment and help generate sleep spindles (Steriade, 1999). During slow wave sleep, the thalamocortical activity consists of synchronous rhythmic activity (EEG delta waves and sleep spindles) associated with burst states in thalamic projection neurons (McCarley et al, 1983). During the awake state there is some sort of cortical activation, presumably related to partial neuronal depolarization bringing neurons closer to firing levels (Steriade, 2000).…”
Section: Sleep-wake Systemsmentioning
confidence: 99%
“…In the awake attentive animal, thalamocortical neurons are relatively depolarized, discharge almost exclusively in the single-spike firing mode, and faithfully transfer inputs from the sensorium. With the transition to slowwave sleep, thalamic neurons hyperpolarize and increasingly replace single-spike discharge with rhythmic burst firing, such as spindle waves (McCarley et al, 1983;Domich et al, 1986;Steriade et al, 1986Steriade et al, , 1993. Spindle waves are observed in the electroencephalogram (EEG) as waxing and waning 6 -15 Hz oscillations (Steriade et al, 1993).…”
Section: Introductionmentioning
confidence: 99%